Computational and Experimental Study on Innovative Horizontal-Axis Wind Turbine Blade Designs - Alsultan, Abdulrahman A. (UWM Digital Commons, 2015)
This study was made to explore three novel blade geometries with intent to increase power production of a horizontal axes, three blade arrangement wind turbine. This was done by designing the blades using computer aided design (CAD) modeling software, followed by a rigorous testing phase, utilizing a computational fluid dynamics software (CFD). The blades then went into a cycle of iterative design to achieve the best parameters that will positively impact the overall power generation efficiency. These steps were followed by printing the blades utilizing 3D Printing technology, testing them for the power generation, and finally, tabulating these findings to validate the numerical results gathered using CFD software. The blade designs under investigation here are the slotted blade (blade with slot shaped cavity on leading edge extending to lower surface), A blade resembling the tubercles (local inflation or bulges on surface) found on a humpback whale and the winglet blade, which was compared to the baseline traditional straight blade. The slotted, tubercle and straight blade were experimentally investigated, while the winglet blade underwent a CFD study only and compared to the other designs. It was found experimentally that the slotted blade generates 26.1% more power on average than the straight blade, and was found very ideal for low wind vacancies, while the tubercle was found of less effectiveness than the straight, though it possesses superior characteristics in suppressing the resultant noise, which is a common wind turbine problem. The winglet showed very similar in results to the straight blade, where its addition would come very fruitful at higher wind velocities, due to the fact that the inertial forces needed to start the operation is a higher order of magnitude than the straight blade.